Siyasah Syariah dan Keadilan Ekologis - Malan, Masfa; Rahmatullah; Nasim, Abu Sahman (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
Nickel mining in Central Halmahera has generated significant ecological impacts, raising fundamental questions regarding ecological justice from the perspective of Siyasah Syariah. This study aims to analyze the compatibility of Indonesia’s nickel downstreaming policy with the principles of Siyasah Syariah and Maqasid al-Shariah in realizing ecological justice. Employing a qualitative approach with normative–juridical analysis, this research integrates the theoretical framework of Siyasah Syariah with empirical data on the environmental impacts of nickel mining. The findings indicate that nickel mining activities in the region have resulted in the degradation of 299 watersheds, deforestation of approximately 27,900 hectares of forest cover, and various forms of environmental pollution, which constitute violations of the principles of hifz al-nafs (protection of life) and hifz al-nasl (protection of progeny) within Maqasid al-Shariah. Although the nickel downstreaming policy has produced short-term economic benefits, it does not fully conform to the principle of maslahah in Siyasah Syariah, as it overlooks distributive justice and ecological sustainability. This study recommends a reformulation of mining policies grounded in Maqasid al-Shariah to promote sustainable ecological justice.